Effectiveness of learning management system, teachers’ techno-pedagogical skills, and students’ learning engagement in Senior High School at the University Of Perpetual Help System-Jonelta Campuses - Samson, Veronica; Yango, Antonio (Technium Social Sciences Journal, 2023)
Information Communication Technology (ICT) changed the world orientation in general and education particularly in the teaching and learning process. A learning management system, or LMS, a software application that allows students to access course resources such as a syllabus, gradebook, discussion boards, and due dates (Center for Innovation in Teaching & Learning, 2021) has been widely utilized in the educational system. Several educational institutions have been using certain LMS in planning, implementing, and evaluating learning processes (Brush, 2020), hence, researches were conducted to determine its effect to the teaching-learning process. However, there were many studies conducted about the effectivity of LMS, teachers’ techno-pedagogical skills, and students’ engagement which were mostly in international settings, but no study yet had been conducted particularly in the province of Laguna and among the senior high school students of UPHS-JONELTA Campuses. Thus, the researcher was inspired to measure the effectiveness of LMS, the teachers’ techno-pedagogical skills and students’ learning engagement and the relationship among variables. This is to further come up with programs that would help improve the utilization of LMS and the pedagogical competence of the teachers to ensure the maximum learning engagement of the learners This study utilized the descriptive-correlational research design which provides the most effective tool for determining the condition of relationship that exist (Bermudo et al., 2018). The respondents of the study consisted of 350 out of 3972 grade 12 students of University of Perpetual Help System JONELTA enrolled during the Academic Year 2022-2023. The sample size was computed using the Raosoft Size Calculator with the confidence level of 95 percent and a margin of error of 5 percent. The respondents were selected by utilizing stratified random sampling strategy. Proportional allocation was employed to calculate the number of the respondents selected from each campus. A total of 44 respondents came from Pangasinan Campus, 16 respondents from Pueblo de Panay Campus, 27 respondents from Isabela Campus, 54 respondents from GMA campus, 42 respondents from Manila campus and 167 respondents from Binan Campus for a total of 350 respondents in all. The research utilized modified standardized tests for the purpose of collecting the needed primary data. The first part covered the level of effectiveness of LMS in terms of system content, instruction, interaction, and technology quality. The second part covered the level of teachers’ pedagogical skills in terms of using technology in teaching; using technology in providing learning experiences; and using technology in preparation. Lastly, the third part of the questionnaire covered the level of students’ learning engagement in LMS. . Furthermore, a pilot test was also conducted and for the reliability of questionnaire using Cronbach Alpha, the results are as follow: for effectiveness of LMS: 0.963; for pedagogical skills: 0.934; and for students’ engagement: 0.950. After some modifications made, it was shown to the adviser for final approval. Based on the findings of the study, the study conclusions were drawn: The level of effectiveness of LMS in terms of system content, instruction, interaction, and technology quality is high. The level of the senior high school teachers’ techno-pedagogical skills alongside with using technology in teaching; using technology in providing learning experiences; and using technology in preparation is very high. The level of the senior high school students’ engagement in LMS is very high. Moreover, it was found out that the higher the level of effectiveness of LMS , the higher the teachers’ level of techno-pedagogical skills. Also, the higher the level of effectiveness of LMS, the higher the level of students’ engagement in LMS. Furthermore, the higher the level of teachers’ pedagogical skills, the higher the level of engagement of the students in LMS. Therefore, the better the skills of the teachers in utilizing technology in teaching, the more the students are engaged in LMS. Lastly, the independent variables; instruction and interaction under the effectiveness of LMS and the overall techno-pedagogical skills of the teachers are the drivers of the level of students’ engagement in LMS in the senior high school.